MEMBANGUN BRANDING ORGANISASI KARANG TARUNA MELALUI SOSIAL MEDIA - Abdul Rahman Kadafi; Indah Purnamasari; Tuslaela Tuslaela (LPPM Universitas Nusa Mandiri, 2022)
The rapid development of technology and information in recent years has made the internet a communication tool that is widely used by the community. In the current pandemic period, where there are social restrictions, social media as a digital means, its presence is very important for all circles of society where one of the benefits of social media is as a promotional/branding media including for promotion of organizations, for example by making posts about activities related to social media. positive activities carried out by the organization on social media. Branding is an effort to promote something by forming a self-image so that it gains the trust of the general public. Karang Taruna is a forum for fostering and developing as well as empowering in an effort to develop productive activities by utilizing all the potential available in the environment, both human resources and natural resources that already exist and the use of the internet as one of its social activities. The Karang Taruna 07 management wanted to build organizational branding, but due to lack of knowledge about the importance of building organizational branding and did not know how to make organizational branding so that the Karang Taruna 07 management did not yet have the Karang Taruna 07 organizational branding. administrators and members of the youth organization about organizational branding and how to manage social media to improve the organization's image. In connection with the Covid19 pandemic, the community service program on